A nonlinear hyper-viscoelastic model for predicting recoverable behavior of largely-deformed asphalt mortar. (21st February 2022) - Bai, Fan; Yang, Xinhua; Zeng, Guowei
Graphical abstract: Highlights: The model follows linear superposition principle in a creep-recovery process. The model and the numerical algorithm automatically preserve objectivity. A systematic approach is proposed to determine the model parameters. The model reasonably predicts the nonlinear viscoelasticity of asphalt mortar. Abstract: For predicting the recoverable behavior of largely-deformed asphalt mortar with geometrical-material nonlinearity and viscoelastic-viscoplastic coupling, a nonlinear hyper-viscoelastic constitutive model is established in the local intermediate configuration based upon the Clausius-Duhem inequality. Although with a stress-dependent parameter to represent the viscoelastic nonlinearity, the proposed model follows the linear superposition principle in a creep-recovery (C-R) process. Based on this feature, recovery curves in C-R tests can be transformed to creep curves for model calibration. It is applied to two types of asphalt mortar labeled AM-1 and AM-2. AM-1 comes from dense-graded asphalt concrete and contains filler, while AM-2 has an idealized gradation and a lower bitumen content. The increasing-stress repeated C-R tests under uniaxial compression are performed for determining model parameters, and the other C-R tests for model validation. A numerical algorithm of the constitutive model is presented and implemented in the ABAQUS finite element (FE) software, in order to validate the constitutive model and the obtained model parameters by comparing the measurements with the FE predictions. Reasonable agreements are found in the comparisons, and the R-squared values are more than 0.7. The determined model parameters show that AM-2 has higher initial moduli and better deformation resistance, but its long-term relative moduli are lower than those of AM-1.